Rise and divine eaudiobook - Harper, Lana (Witches of Thistle Grove, 2024)
To save both her town and the woman who loves her against all odds, a witch haunted by loss must reckon with her turbulent past, in the next magical romance in the Witches of Thistle Grove series by New York Times bestselling author Lana Harper.   Even in a family of chaotic necromancers, Daria “Dasha” Avramov has always been an outlier. An event planner at the Arcane Emporium occult megastore, Dasha is also a devil eater: a rare necromantic witch with an affinity for banishing demons and traversing the veil, the boundary between this realm and the next.    Still grieving the loss of both beloved parents years ago, and plagued by a dangerous obsession with the world beyond the veil, Dasha is fiery yet guarded, an expert at dodging commitment. Her worst regret is a devastating breakup with the wise, empathetic, and sensual Ivy Thorn, her event-planning counterpart at Honeycake Orchards, and probably the love of Dasha’s life. Dasha has managed to break Ivy’s heart not once, but twice, so things are more than a little tense between them.   When they’re thrown together to plan the Cavalcade—a month-long festival celebrating Thistle Grove’s ceremonial founding with dazzling spectacles held by the town’s witch families—Dasha hopes that the third time might be the charm, while Ivy refuses to let herself be hurt again. As they confront the pain and passion lingering between them, Dasha and Ivy must also stand against an otherworldly threat unlike anything Thistle Grove has faced before.